Cost-effectiveness analysis of pembrolizumab vs. chemotherapy as second-line treatment for advanced esophageal carcinoma in the United States - Hu, Jia; Ye, Zhuomiao; Xu, Zhe; Hao, Zhinan; Wang, Yongjun (Frontiers in Public Health, 2022)
Background The national Comprehensive Cancer Network has suggested pembrolizumab as a second-line therapy for esophageal squamous cell carcinoma (ESCC) patients with a programmed death ligand-1 (PD-L1) combined positive score (CPS) ≥ 10. However, despite the increased survival rate associated with pembrolizumab in these patient population, the high cost of pembrolizumab may influence its antitumor effect. This study aimed to evaluate the cost-effectiveness of pembrolizumab compared to chemotherapy as second-line treatments for esophageal carcinoma (EC) based on KEYNOTE-181 trial. Methods A Markov model was constructed using TreeAge 2021 based on three different groups: all intent-to-treat patients (ITT population), patients with ESCC (ESCC population), and patients with a PD-L1 CPS ≥10 (CPS ≥10 population). Incremental cost, Incremental effect, Life-years, quality-adjusted life-years (QALYs) and incremental cost–effectiveness ratio (ICER) were calculated. Analyses were conducted on the setting of a willingness-to-pay threshold of 150,000 from the US perspective. Results The ICERs for pembrolizumab were 157,589.545 per QALY, 60,238.823 per QALY, and 100,114.929 per QALY compared with chemotherapy in the ITT, ESCC, and CPS≥10 populations, respectively. The ICER of the ITT population was higher than 150,000, suggesting that pembrolizumab was not a cost-effective treatment scheme in patients with a PD-L1 CPS ≤ 10 or esophageal adenocarcinoma. The ICER was < 150,000 in the ESCC and CPS≥10 populations, indicating that pembrolizumab was cost-effective in these two subgroups. Conclusion The determining of pembrolizumab as a cost-effective second-line therapy for EC in the United States depends on the histologic type and PD-L1 expression.